Untangling "NETosis" from NETs. Issue 2 (15th January 2019) - Yousefi, Shida; Stojkov, Darko; Germic, Nina; Simon, Dagmar; Wang, Xiaoliang; Benarafa, Charaf; Simon, Hans‐Uwe
Abstract: Neutrophil extracellular trap (NET) formation is a cellular function of neutrophils that facilitates the immobilization and killing of invading microorganisms in the extracellular milieu. To form NETs, neutrophils release a DNA scaffold consisting of mitochondrial DNA binding granule proteins. This process does not depend on cell death, but requires glycolytic ATP production for rearrangements in the microtubule network and F‐actin. Such cytoskeletal rearrangements are essential for both mitochondrial DNA release and degranulation. However, the formation of NETs has also been described as a distinct form of programed, necrotic cell death, a process designated "NETosis." Necrotic cell death of neutrophils is associated with the permeabilization of both plasma and nuclear membranes resulting in a kind of extracellular cloud of nuclear DNA. The molecular mechanisms eliciting necrotic neutrophil death have been investigated and appear to be different from those responsible for NET formation following mitochondrial DNA release. Here, we discriminate between the mechanisms responsible for the release of mitochondrial versus nuclear DNA and address their respective functions. Our aim is to clarify existing differences of opinion in the fields of NET formation and neutrophil death. Abstract : NETs are formed by activated neutrophils releasing mtDNA and granule proteins. This process requires an active NADPH oxidase and glycolytic ATP production for rearrangements of the cytoskeleton network in order to relocate granules and mitochondria.